2019
DOI: 10.1097/sla.0000000000002775
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery (ERAS) Pathway in Esophagectomy

Abstract: The results of this study seem to be clinically meaningful and in line with those from other studies. The initial validation revealed good predictive properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…There are many reasons for a delayed recovery after surgical resection of esophageal cancer. In a recent study, Parise et al [25] reported that prolonged stay after esophagectomy was associated with both the patient clinical characteristics (ASA score > 3, failure of postoperative mobilization) and factors related to the operation (surgery duration > 255 min and "non-hybrid esophagectomy"). Therefore, an optimal ERAS protocol should include a wide spectrum of perioperative elements.…”
Section: Discussionmentioning
confidence: 99%
“…There are many reasons for a delayed recovery after surgical resection of esophageal cancer. In a recent study, Parise et al [25] reported that prolonged stay after esophagectomy was associated with both the patient clinical characteristics (ASA score > 3, failure of postoperative mobilization) and factors related to the operation (surgery duration > 255 min and "non-hybrid esophagectomy"). Therefore, an optimal ERAS protocol should include a wide spectrum of perioperative elements.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the application of Enhanced Recovery after Surgery (ERAS) programs for esophagectomy is associated with favorable overall morbidity and mortality, and reduced hospital length of stay [3540]. However, the methodological quality of these studies is limited [4142]. Identifying a clinically relevant CRP cut-off may be a helpful adjunct to the fast-track pathways by providing an early alert for leakage, selecting patients for diagnostic studies, and tailoring the therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…However, as this was the first time that LGE was implemented occurred at the beginning of the learning, the operation duration was still close to that of existing esophagectomy approaches 4 . In a recent study by Parise et al, 9 a surgical duration of over 255 minutes predicted operative morbidity and prolonged postoperative length of stay. Hence, LGE may result in better surgical outcomes as the operation time shortens as more experience with the procedure is gained.…”
Section: Commentsmentioning
confidence: 72%
“…Transmediastinal esophagectomy obviates the need for entry into the pleural cavity 8 but only provides a narrow working space for multiple surgical instruments 4 . Expansion of the surgical field, which aims to reduce instrumental collision and improve visualization within the mediastinum, can be realized by the introduction of an artificial pneumomediastinum 9 . However, CO 2 insufflation into the mediastinum may also lead to hemodynamic instability and therefore add potential risks to cardiopulmonary complications 5 …”
Section: Commentsmentioning
confidence: 99%